Targeted killing of rhabdomyosarcoma cells by a MAP-based human cytolytic fusion protein. Issue 2 (1st September 2015) - Brehm, Hannes; Hristodorov, Dmitrij; Pardo, Alessa; Mladenov, Radoslav; Niesen, Judith; Fischer, Rainer; Tur, Mehmet K.; Barth, Stefan
Highlights New, fully human cytolytic fusion protein based on a microtubule-associated protein (MAP) targeting fetal acetylcholine receptor by scFv35. scFv35-MAP specifically bound to and was rapidly internalized in RMS cells. scFv35-MAP was able to kill RMS cells by apoptosis. We are the first to show the efficacy of a fully hCFP on RMS cells. Additionally we show the efficacy of MAP on another tumor entity.